Sport injuries in elite amputee football players - Wieczorek, J.; Wieczorek, A.; Bauerfeind, J.; Grzelinska, P.; Sliwowski, R.; Tasiemski, T. (Central European Journal of Sport Sciences and Medicine, 2017)
Despite many previous studies dealing with various aspects of physical activity in individuals with an amputation, the risk of injury in amputee footballers has not been assessed thus far. The aim of this study was to characterize the incidence and causes of sport injuries experienced by amputee football players. Furthermore, the incidence of injuries was stratified according to the players` level of competitive aggressiveness and anger, and their role in the field. The study included 21 members of the Polish National Amputee Football Team, who have been followed-up for a period of 6 months. A total of 16 injuries were recorded, including three that required a medical consultation: luxation of the left elbow, adductor strain and ankle sprain. The group of injuries that have not been consulted with a physician included muscle strains (n = 4), abrasions (n = 3), bruising (n = 3), joint subluxations (n = 2) and luxation (n = 1). The injuries turned out to be more frequent in the lower limbs (n = 10) than in the upper ones (n = 6). The risk of injury turned out to be higher during trainings (n = 9) than matches (n = 7). Amputee football seems to be associated with low risk of injury, since only several bodily contusions were documented throughout the study period. The injuries occurred in 38% of the players; this makes amputee football a relatively safe discipline which can be recommended to physically disabled persons.